2007
DOI: 10.1007/s11661-007-9255-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al Addition on Glass Forming Ability and Glass Stability of Ca-Mg-Zn-Cu Based Bulk Metallic Glasses

Abstract: The effect of Al addition on glass forming ability (GFA) and stability of the glassy phase against crystallization was studied for Ca-Mg-Zn, Ca-Mg-Cu, and Ca-Mg-Zn-Cu alloys. The glassy alloys were produced by copper mold casting as wedge-shaped samples with thicknesses varying from 0.5 to 10 mm. Thermal properties, such as glass transition, crystallization and melting temperatures, as well as heats of crystallization and melting, were determined for the produced glasses. Partial substitution of Zn or Cu with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Compared to other metallic glasses: La55Al25Ni20 (m = 42, F1 = 0.455), La55Al25Ni10Cu10 (m = 35, F1 = 0.540) [11], the alloy GdYScAlCo shows rather high values in frazilite and the F1 parameter, which indicates its good glass forming ability.…”
Section: ๐›พ = ๐‘‡ ๐‘ฅ (๐‘‡ ๐‘™ + ๐‘‡ ๐‘” )mentioning
confidence: 84%
See 1 more Smart Citation
“…Compared to other metallic glasses: La55Al25Ni20 (m = 42, F1 = 0.455), La55Al25Ni10Cu10 (m = 35, F1 = 0.540) [11], the alloy GdYScAlCo shows rather high values in frazilite and the F1 parameter, which indicates its good glass forming ability.…”
Section: ๐›พ = ๐‘‡ ๐‘ฅ (๐‘‡ ๐‘™ + ๐‘‡ ๐‘” )mentioning
confidence: 84%
“…The parameter F1, introduced by Senkov [11], is an indicator of glass-forming ability, which establishes a correlation between the fragility parameter and the critical cooling rate at which the amorphous state is formed. The value F1 = 0 corresponds to an extremely fragile liquid, and F1 ~ 0.8 -extremely strong liquid.…”
Section: ๐›พ = ๐‘‡ ๐‘ฅ (๐‘‡ ๐‘™ + ๐‘‡ ๐‘” )mentioning
confidence: 99%
“…3, Fig. 4) [4]; [5]; [22] Selected samples were studied with corrosion tests. The potentiostatic studies have shown some characteristic features that prove the formation of the passive layer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The master alloy with a nominal composition of Ca 50 Mg 20 Zn 12 Cu 18 in atomic percent was used. Alloy ingot was produced by induction melting mixtures of pure elements (Ca 99.5%, Mg 99.8%, Zn 99.995%, Cu 99.95%) and Mg69Ca31 alloy under an argon atmosphere [4]; [5]; [21]. Then the pieces of the ingot (W1 sample) were remelted several times to ensure chemical homogeneity [3]; [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation